CD14 receptor-mediated uptake of nonopsonized Mycobacterium tuberculosis by human microglia. - Peterson, P K (1995)
This study was carried out to determine the role of CD14 receptors in the uptake of nonopsonized Mycobacterium tuberculosis by human microglia. Treatment of microglial cell cultures with antibodies to CD14 or with soluble CD14 significantly blocked infection by M. tuberculosis H37Rv, suggesting that CD14 receptors could facilitate entry of nonopsonized tubercle bacilli into macrophages within the brain.